Investigation of plasma polymerized pyrrole under various gas flow rates and input power using atmospheric pressure plasma jets. (3rd July 2017) - Kim, Dong Ha; Park, Choon-Sang; Kim, Won Hyun; Hong, Jung Goo; Shin, Bhum Jae; Park, Tae Seon; Tae, Heung-Sik
ABSTRACT: This paper has investigated the synthesis of plasma-polymerized pyrrole (pPPy) nano-particles grown by the proposed atmospheric pressure plasma jets (APPJs) through the parametric studies, especially input power and gas flow rate. The transition of conventional streamer-like into intense and glow-like discharges necessary for fully cracking the monomer was observed to be strongly dependent on both input power and gas flow rate. The intense and glow-like discharge was produced only when adopting the specific parametric condition, i.e., a gas flow rate of 1600 sccm and input power with 12.5 kV, thereby resulting in obtaining the synthesized pPPy nano-particle structures with highly cross-linked networks and many double bonds. The plasma-flow characteristics were investigated based on the non-plasma flow numerical simulation, and also analyzed by the voltage, current, infrared, and optical emission spectroscopy (OES). The synthesized pPPy films were analyzed by field-emission scanning electron microscopy (FE-SEM) and Fourier infrared spectroscopy (FT-IR). It is anticipated that the high-quality plasma polymer grown by the proposed APPJs contributes to serving as conducting electrode-materials of a flexible polymer light emitting diode (P-LED).